Interview with Liv Ulmann, actress, activist for UNICEF. . Transcripts in archive M. Bouvard - Bouvard, Marguerite Guzmán.
Interview with Liv Ulmann, actress, activist for UNICEF. Transcripts in archive M. Bouvard.